Analisis Hubungan Pelaksanaan Supervisi Terhadap CPPT di Rumah Sakit Umum Universitas Riau - Vivi Wanti; Yulastri Arif; Dewi Murni (Malahayati Nursing Journal, 2023)
ABSTRACT Documentation is a means of affective communication between health professions. The low quality of integrated record documentation in Indonesia includes incomplete CPPT where patient identity, date and time of visit are not filled in, PPA's signature and full name, and lack of discipline in filling out medical records by PPA. Supervision is carried out in stages in the preparation, implementation and evaluation phases. The preparation phase contains the planning of the supervision program that will be carried out. The implementation phase is the nurse's assessment by the supervisor while the last phase is the evaluation of the supervision assessment (from the results of direct and indirect observations from the CPPT. The purpose of the thesis is to analyze the relationship between the implementation of supervision on CPPT at the Riau University General Hospital. This study was conducted with a cross sectional approach and is a quantitative study. The research sample is 33 people with total sampling sampling technique. The study uses questionnaires and observation sheets that have been tested for validity and reliability. Through statistics there is a relationship between the preparation phase (p value 0.000), the implementation phase (p value 0.001) and the evaluation (p value 0.000) clinical supervision model 4S with CPPT. Researchers recommend the role of supervision to improve service quality and completeness of integrated recording documentation, carried out by increasing the frequency of supervision and assessment of the implementation of the document integrated logging entity. Keywords: Supervisor Characteristics, Supervision 4S model   ABSTRAK Dokumentasi adalah sarana komunikasi afektif antar profesi kesehatan. Rendahnya kualitas pendokumentasian catatan terintegrasi di Indonesia   meliputi tidak lengkapnya CPPT dimana tidak terisinya identitas pasien, tanggal dan jam visite, tanda tangan PPA serta nama dengan lengkap, serta kurangnya kedisiplinan pengisian rekam medis oleh PPA. Supervisi dilakukan bertahap dalam fase persiapan, pelaksanaan dan evaluasi. Fase persiapan berisi perencanaan program supervisi yang dijalankan. Fase pelaksanaan merupakan penilaian perawat oleh supervisor sedangkan fase terakhir adalah evaluasi dari penilaian supervisi (dari hasil observasi langsung dan tidak langsung dari CPPT. Tujuan tesis adalah menganalisis hubungan pelaksanaan supervisi terhadap CPPT di Rumah Sakit Umum Universitas Riau. Penelitian ini dilakukan dengan pendekatan cross sectional dan merupakan penelitian kuantitatif. Sampel penelitian sebanyak 33 orang dengan teknik pengambilan sampel total sampling. Penelitian menggunakan kuesioner dan lembar observasi yang sudah teruji validitas dan reliabilitasnya. Melalui statistik terdapat hubungan fase persiapan (p value 0,000), fase pelaksanaan (p value 0,001) dan fase evaluasi (p value 0,000) supervisi klinik model 4S dengan CPPT. Peneliti merekomendasikan peran supervisi untuk meningkatkan kualitas pelayanan dan kelengkapan pendokumentasian pencatatan terintegrasi, dilakukan dengan cara peningkatan  frekuensi pengawasan dan penilaian terhadap pelaksanaan pendokumentasian pencatatan terintegrasi. Kata Kunci: Karakteristik Supervisor, Supervisi model 4S